2012
DOI: 10.1522/030430421
|View full text |Cite
|
Sign up to set email alerts
|

conséquences à long terme des inondations de juillet 1996 sur la santé biopsychosociale des adultes agés de 50 ans ou plus /

Abstract: RESUMELa présente étude a permis de recueillir des informations auprès de 17 adultes âgés de 50 ans ou plus, vivant seuls ou en couple, avec ou sans enfants, propriétaires de leur résidence et ayant été victimes des inondations de juillet 1996 à Saguenay. Afin de réaliser cette étude, la méthode qualitative utilisant des entretiens comprenant des questions semi-dirigées a été privilégiée pour recueillir les propos des répondants. Les objectifs au nombre de deux étaient les suivants : 1) identifier les sentimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 67 publications
(149 reference statements)
1
4
0
Order By: Relevance
“…Indeed, respondents generally perceived that changes in their spousal and family relationships had been positive, due to a strengthening of ties following the earthquake. This finding has been noted previously in the literature 29 and cited as a protective factor because the presence of effective social support favors the recovery of disaster survivors. 80 , 81 Nevertheless, many participants also reported a decrease in social activity and physical exercise.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Indeed, respondents generally perceived that changes in their spousal and family relationships had been positive, due to a strengthening of ties following the earthquake. This finding has been noted previously in the literature 29 and cited as a protective factor because the presence of effective social support favors the recovery of disaster survivors. 80 , 81 Nevertheless, many participants also reported a decrease in social activity and physical exercise.…”
Section: Discussionsupporting
confidence: 82%
“…In line with the literature on the medium-term impacts of disaster events on survivors, 11 , 29 , 70 - 72 the results of the present study show that participants experienced a deterioration of their health, both physical (hypertension, shingles [herpes zoster], physical fatigue, muscle and bone pain, erythroderma, cancer) and psychological (sleep disorders, depression, stress, fear, hypervigilance, stress and anxiety, panic anguish, loss of motivation), following the disaster event (see Table 4 ). Previous studies have also identified some of these same health problems as consequences of exposure to disaster events, including hypertension, fatigue, stress and anxiety, as well as sleeping disorders.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations